MULTIDISCIPLINARY APPROACHES TO THE INTRODUCTION OF THE CREDIT-MODULE SYSTEM IN VOCATIONAL EDUCATIONAL INSTITUTIONS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article examines the implementation of the credit-module system (CMS) in vocational education institutions through a multidisciplinary approach. The study highlights how modularization and competency-based learning can integrate diverse disciplines to create holistic educational experiences. Emphasis is placed on designing interdisciplinary curricula, adopting innovative pedagogical methods such as project-based learning and blended education, and leveraging emerging technologies like virtual reality and artificial intelligence. The article also explores collaboration with industry partners to ensure alignment with labor market needs and addresses the challenges associated with implementing CMS. By adopting a multidisciplinary approach, vocational education institutions can prepare students for complex, interconnected professional environments, equipping them with both technical and transferable skills essential for modern careers.